ChemInform Abstract: An Air‐Stable Copper Reagent for Nucleophilic Trifluoromethylthiolation of Aryl Halides. Issue 21 (2nd May 2013) - Weng, Zhiqiang; He, Weiming; Chen, Chaohuang; Lee, Richmond; Tan, Davin; Lai, Zhiping; Kong, Dedao; Yuan, Yaofeng; Huang, Kuo‐Wei
Abstract This article describes readily available copper trifluoromethylthiolate complexes, which react with a wide range of aryl and heteroaryl halides to give the respective trifluoromethyl thioethers in good yields.